Analysis of students critical thinking ability based on gender in science learning environmental pollution topics - Siska Oktafiana Dewi; Erman Erman (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to describe the differences in the critical thinking ability of male and female students at junior high school (SMPN 27 Surabaya) on environmental pollution topics. The type of research used is descriptive. The research sample was 34 students of SMPN 27 Surabaya class VII F consisting of 17 female students and 17 male students. Data collection was carried out using critical thinking skills tests, student questionnaires, and learning observation sheets. The data obtained include students' critical thinking skills, observation results, and interview results that have been grouped based on the student's gender. The results of this study show that there are differences in critical thinking skills between male students and female students. Female students scored an average critical thinking ability of 75, while male students scored 65. The critical thinking ability of female students is higher than that of male students, as evidenced by the average score of female students being higher than that of male students. It shows that in learning activities, teachers must pay attention to student gender differences, motivate students, and choose the appropriate learning model.